Mobile Learning Model of Tour Guide Business in Universities from the Perspective of Distributed Cognition - Chuanhong Lin; Liangju Wang; Yamei Li (Discrete Dynamics in Nature and Society)
In order to promote the better development of tour guide business, this article takes the tour guide business teaching in colleges and universities as an example and analyzes the current situation and the effect of students’ learning in the tour guide business course through investigating and researching the current situation of ideological and political teaching of the tour guide business course. It also proposes corresponding improvement measures for the existing problems, so as to improve the ideological and political teaching effect of the tour guide business course. To this end, this study relies on the powerful functions of UMU platform and builds a hybrid mobile learning mode based on UMU platform by improving the traditional teaching method of “face to face instruction + online lecture.” Although the UMU-based blended mobile learning model is formally divided into online learning and offline activities, in the actual teaching process, there are both you and me. In the process of online learning, students can realize the convenient learning through mobile APP terminal anytime and anywhere, or they can sit comfortably at the study table through the computer; in the offline activity classroom, students can sit in the classroom of UMU and communicate with teachers face to face, or they can use their cell phones to project their check-in, opinions, test results, etc. to the big screen. In the whole UMU-based hybrid mobile learning model, there is no clear boundary between online learning and offline activities, and online and offline are integrated with each other and crossed according to the actual learning needs to maximize learning efficiency.